Table 5_Specialized Bacteroidetes dominate the Arctic Ocean during marine spring blooms.docx - Álvaro Redondo-Río; Christopher J. Mundy; Javier Tamames; Carlos Pedrós-Alió (2024)
A metagenomic time series from Arctic seawater was obtained from Dease Strait, to analyse the changes in bacterioplankton caused by the summer phytoplankton bloom. Bacterial clades specialized in the metabolism of polysaccharides, such as Bacteroidetes, became dominant along the bloom. These specialized taxa quickly displaced the microbial clades that dominate nutrient-poor waters during early spring, such as Archaea, Alpha-and Gammaproteobacteria. At the functional level, phyla Bacteroidetes, Planctomycetes, and Verrucomicrobia showed higher contents of polysaccharide-degradation functions. The Bacteroidetes community shifted toward species with higher polysaccharide-degrading capabilities, targeting algal polysaccharides in summer. Regarding transporters, Bacteroidetes dominated SusC-TonB transporters and had an exclusive family of glycoside-binding proteins (SusD). These proteins were used to identify polysaccharide-utilization loci that clustered transporters and polysaccharide-active enzymes, showing a higher level of specialization toward polysaccharide use. Altogether, these genomic features point to the genetic adaptations that promote the dominance of Bacteroidetes during phytoplankton blooms.